Evaluation of the development potential of rooftop solar photovoltaic in Taiwan. (April 2015) - Ko, Li; Wang, Jen-Chun; Chen, Chia-Yon; Tsai, Hsing-Yeh
Abstract: Because of extensive exploitation, fossil fuels are gradually becoming depleted and global warming issues are increasing. Therefore, all nations must develop alternative energy resources to reduce the potential risk of exhausting the available fossil fuel energy supply and to resolve environmental degradation. The amount of sunlight and installed power capacity are crucial factors that influence solar photovoltaic (PV) efficiency. Among domestic and international studies, numerous scholars have proposed various installed power capacity assessment models, which typically calculate areas based on sub-fields, ground floors or per capita. However, an evaluation of the potential of solar PV power generation on rooftops indicated that the shadow effect caused by building structures substantially influence the amount of installed power capacity. This study aims to effectively compute the shadow areas (shaded areas) on rooftops. By using the Hillshade module, the buildings' elevation data and the solar azimuth and altitude angles at different hours were calculated to obtain the hourly sun/shade grayscale values. The grayscale values were then integrated into binary images to calculate the shadow areas on rooftops. This study suggests that the rooftop solar photovoltaic installation capacity is some 12, 428.5 MW and power generation capacity 15, 423.75 GWh in Taiwan. Highlights: Taiwan is an isolated electric power system. Taiwan sunlight is strong and thus developing solar energy is viable. The solar azimuth and altitude angles obtained the grayscale values. The rooftop solar photovoltaic installation capacity is some 12, 428.5 MW.